Overview on agent application to support collaborative learning interaction - Erlin, Erlin (2007)
Collaborative learning involves students working to gether to aid their learning and is considered an effective method to implement learning goal. However, it involves complicated processes such as have inconvenient assistance to manage the increasing demand for information and support extension of interaction and how to activate collaboration interaction and communication between different types of interactions. A collaborative learning model based on agent can improve learning effectiveness and give good impact to learning process. This paper discusses the definition, classification and roles of agent to support collaborative learning interaction in E-learning. It overviews the rapidly use of agents to support collaborative learning and describes the types of interaction and communication tools to enhance interaction between all participants. We identify three types of major agents used in collaborative learning interaction; interface agent, information and internet agent, and collaborative agent